Market devotion: understanding the Ram Mandir event influence on the Indian stock market using event study method - Richa Goel; Anindita Bhattacharjee; Neeru Sidana; Tilottama Singh; Manleenjot Kaur (Journal of Applied Economics)
This study attempts to find out how important socio-religious events affect financial markets, with particular emphasis on the Ram Mandir event in India. This study uses the Event Study Method to analyse how the inauguration of the Ram Mandir, a historic event with great cultural, religious and political importance, affected the Indian stock market. This study gauges the response of the Indian stock market to the Ram Mandir event using the Market Model with a robust empirical framework. The results of the study indicate that the Ram Mandir event influenced investors behaviour and mood of the market causing significant changes in stock market. Furthermore clarified by the study are the duration and intensity of market reactions throughout various event timeframes. The insight gained from this study will be very helpful to investors, financial analysts, and policymakers interpreting the consequences of socio-religious events on financial markets.